Nerve Growth Factor Pathobiology During the Progression of Alzheimer’s Disease - Mufson, Elliott J.; Counts, Scott E.; Ginsberg, Stephen D.; Mahady, Laura; Perez, Sylvia E.; Massa, Stephen M.; Longo, Frank M.; Ikonomovic, Milos D. (Frontiers in Neuroscience, 2019)
The current review summarizes the pathobiology of nerve growth factor and its cognate receptors during the progression of Alzheimer’s disease (AD). Both protein and transcript data indicate that cholinotrophic neuronal dysfunction is related to an imbalance between TrkA-mediated survival signaling and proNGF/p75NTR-mediated pro-apoptotic signaling, which may be related to alteration in the metabolism of NGF. Data indicate a spatiotemporal pattern of degeneration related to the evolution of tau pathology within cholinotrophic neuronal subgroups located within the nucleus basalis of Meynert (nbM). Despite these degenerative events the cholinotrophic system is capable of cellular resilience and/or plasticity during the prodromal (and later stages of the disease. In addition to neurotrophin dysfunction, studies indicate alterations nuclear epigenetic proteins occur within cholinotrophic nbM neurons during the progression of AD, suggesting a mechanism that may underlie changes in transcript expression. Findings suggest that postmortem intraventricular or premortem CSF levels of proNGF mark the onset of MCI and the transition to AD suggesting this proneurotrophin to be a potential biomarker for the progression of MCI. Novel therapeutics to treat NGF dysfunction included NGF gene therapy and the development of small molecule agonists for the high affinity TrkA survival receptor and antagonists against the low affinity p75NTR death receptor for the treatment of AD.